Cardiac disease in systemic lupus erythematosus: prospective study of 70 patients. Issue 2 (February 1992) - Cervera, R; Font, J; Paré, C; Azqueta, M; Pérez-Villa, F; López-Soto, A; Ingelmo, M
Abstract : A prospective two dimensional and Doppler echocardiographic study of 70 consecutive patients with systemic lupus erythematosus (SLE) and 40 controls was carried out. Forty patients (57%) were found to have echocardiographic disturbance. Valvular abnormalities were detected in 31 patients (44%) and in only two controls (5%). Mitral valve abnormalities were the most common findings (23/70 (33%)) with mild or moderate regurgitation the most frequent lesion (16% and 9% respectively). Three patients (4%) had a morphological echocardiographic pattern suggestive of non-infective verrucous vegetations affecting the mitral valve. No patient had haemodynamically significant clinical valve disease. Pericardial effusion was identified in 19 patients (27%), of whom 14 had mild and clinically silent disease. Myocardial abnormalities were found in 14 patients (20%), but clinical features of myocardial dysfunction were present in only one. Patients with antiphospholipid antibodies were found to have an increased prevalence of endocardial lesions, mainly valvular regurgitation. It is concluded that the inclusion of echocardiography in a study protocol of patients with SLE can identify an important subset of patients with cardiac abnormalities, many of which are clinically silent. In addition, the association of antiphospholipid antibodies with endocardial lesions suggests that these antibodies may have a prominent role in the pathogenetic mechanisms of heart valve disease in SLE.